The genus Ommatidiotus Spinola (Hemiptera: Auchenorrhyncha: Caliscelidae) from the Korean Peninsula and neighboring countries - Park, Jaekook; Jung, Sunghoon (Zootaxa, 2024)
A total of four species of the caliscelid genus Ommatidiotus Spinola (Hemiptera: Auchenorrhyncha: Caliscelidae) are reviewed from the Korean Peninsula and neighboring countries, based on specimens housed in Hokkaido University, Japan. The Transpalearctic species O. dissimilis (Fallén) is recorded from the Korean Peninsula for the first time, and the distributions of O. karafutonis stat. rev. and O. nigritus are discussed. We also provided photographs of the type specimens and redescriptions, and a key to the genus Ommatidiotus species from Northeast Asia.